Snowpack properties vary in response to burn severity gradients in montane forests. (23rd December 2019) - Maxwell, Jordan; St Clair, Samuel B
Abstract: Wildfires are altering ecosystems globally as they change in frequency, size, and severity. As wildfires change vegetation structure, they also alter moisture inputs and energy fluxes which influence snowpack and hydrology. In unburned forests, snow has been shown to accumulate more in small clearings or in stands with low to moderate forest densities. Here we investigate whether peak snowpack varies with burn severity or percent overstory tree mortality post-fire in a mid-latitude, subalpine forest. We found that peak snowpack across the burn severity gradients increased 15% in snow-water equivalence (SWE) and 17% in depth for every 20% increase in overstory tree mortality due to burn severity. Snowpack quantity varied greatly between the two winter seasons sampled in this study with 114% more snow in 2016 versus 2015, yet the effect of burn severity on snowpack remained consistent. These data support previous studies showing increases in peak snow depth and SWE in burned forests but for the first time provides novel insights into how snow depth and SWE change as a function of burn severity. We conclude that changes not only in the frequency and size of wildfires, but also in the severity, can alter peak snow depth and SWE, with important potential implications for watershed hydrology.